Serum Interleukin-6 (IL-6) Level and Glycemic Control of Covid-19 Exposed Diabetic Patients in a Selected District Diabetic Hospital of Bangladesh - Islam, Meer Faizul; Rahman, Md. Ashiqur; Hossain, Md. Biplob; Islam, Sadia; Haque, Afrin; Rahaman, Shohanur; Mahbub, Chomel; Akram, Arifa (Bangladesh Journal of Infectious Diseases, 2025)
Background: The COVID-19 pandemic worsened diabetes management, increasing the risk of complications like DKA and HHS, requiring close blood glucose monitoring. Objective: The objective of this study was to examine the relationship between serum IL-6 levels and glycemic control in COVID-19-exposed diabetic patients in Bangladesh. Methodology: This cross-sectional study was conducted at Ahad Diabetic Health Complex, Jessore, from October 2022 to May 2023, involving 85 diabetic patients aged 18 and above, exposed to COVID-19. Data on socio-demographics, glycemic status, and COVID-19 exposure were collected using a semi-structured questionnaire. Blood samples were taken for serum interleukin 6 (IL-6) analysis. The study followed ethical guidelines, with approval from relevant ethical review committees, and used SPSS for statistical analysis. Results: Among the respondent’s majority were middle and elderly age group people with mean 8.0741±11.45401years with almost equal male female ratio. By nutritional status 48.2% were of Normal weight, followed by 43.5% were Pre obese, and 4.7% were obesed. Among the respondents 52.9% cases had family history of diabetes, 41.2% caseshad COVID symptoms but only 17.6% were COVID-19 positive with having COVID symptoms. Among the respondents, 60.0% were suffering from diabetes for 1 to 5 years, 28.2% for 6 to 10 years, 7.1% for 11 to 15 years and only 4.7% were suffering for 13 – 20 years. The mean Serum IL-6 was 5.66±2.245 among the respondents having COVID-19 positive while it was more 7.10±6.137 among the rests. Mean blood glucose level was 14.7933±7.45381 mmol/L who were COVID-19 positive and 12.9876±5.69122 mmol/L among rests. Conclusion: The study found a significant association between serum IL-6 levels and age, suggesting that age may influence inflammation in COVID-19-exposed diabetic patients. Bangladesh Journal of Infectious Diseases, December 2024;11(2):131-137